1992
DOI: 10.1200/jco.1992.10.1.79
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of radiation-induced downstaging of rectal cancer by fluorouracil and high-dose leucovorin chemotherapy.

Abstract: Despite the fact that patients who received chemotherapy (group 1) had more advanced disease compared with those with resectable disease (group 3), the addition of LV/5-FU increased the resectability and downstaging rates. The ultimate impact of a complete response as well as a decrease in the incidence of pelvic nodes on local control and survival remains to be determined. However, given the enhancement of down-staging in patients with unresectable rectal cancer, we are encouraged by the combined modality app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
72
0
7

Year Published

1996
1996
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 242 publications
(83 citation statements)
references
References 16 publications
4
72
0
7
Order By: Relevance
“…Complete pathlogic response in patients receiving preoperative radiation and chemotherapy for rectal carcinoma ranges from 24 to 30% in other studies. [42][43][44][45][46][47] Therefore, it is not unrealistic to expect long-term control in these patients. Patients treated purely for palliation achieve long-term symp-tom control, especially for pelvic pain, which can be severely debilitating and affect the quality of life of most patients with recurrent carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Complete pathlogic response in patients receiving preoperative radiation and chemotherapy for rectal carcinoma ranges from 24 to 30% in other studies. [42][43][44][45][46][47] Therefore, it is not unrealistic to expect long-term control in these patients. Patients treated purely for palliation achieve long-term symp-tom control, especially for pelvic pain, which can be severely debilitating and affect the quality of life of most patients with recurrent carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, radiotherapy alone or in combination with chemotherapy is used prior to surgery to reduce the tumor size. Extensive studies on the use of (chemo) radiotherapy for these tumors showed that preoperative radiotherapy decreases local recurrence rates by 50 to 60% as compared with surgery alone (43)(44)(45)(46)(47)(48)(49), and the addition of chemotherapy to radiotherapy has been shown to further increase local control (50)(51)(52)(53)(54). On the basis of these results, the current standard treatment of locally advanced rectal cancer consists of preoperative chemoradiation followed by total mesorectal excision surgery.…”
Section: Clinical-translational Advancesmentioning
confidence: 99%
“…The antimetabolite 5-FU plays a central role in the treatment of colorectal cancer and, additionally, was shown to enhance the effectiveness of radiation therapy in the treatment of rectal cancer [2,3] . One of the most important molecular targets of 5-FU is thymidylate synthase (TS), which is essential for the de novo DNA synthesis [4] .…”
Section: Introductionmentioning
confidence: 99%